Preliminary Identification of Central Auditory Processing Screening Tests for Individuals with Multiple Sclerosis - Lewis, M. Samantha; Wilmington, Debra; Hutter, Michele; McMillan, Garnett; Casiana, Linda; Fitzpatrick, Mary; Lilly, David J.; Bourdette, Dennis; Folmer, Robert; Fausti, Stephen (Seminars in Hearing, 2012)
Research suggests that individuals with multiple sclerosis (MS) may be susceptible to deficits in central auditory processing (CAP). Audiologists need to be able to select appropriate tests to screen for such deficits in this patient population. The purpose of this report is to identify promising CAP tests for screening patients with MS. A comprehensive behavioral CAP test battery was administered to 26 subjects with MS and 27 subjects without MS. Out of six potential tests, selected based on the CAP deficits reported in the scientific literature, results suggest that the Staggered Spondaic Word test and the SCAN-A, followed by the Masking Level Difference test, are the most promising screening tests in this patient population. The Frequency Patterns Test, the Dichotic Digits Test, and the Gaps-in-Noise Test, on the other hand, were less promising. It should be noted, however, that this is a preliminary analysis, and that no clinical recommendations can be made until the reference standards are established in a much larger sample population.
Keywords: multiple sclerosis; hearing loss; central auditory processing